Sultan Ahmad Shah’s demise a huge loss to UMP - UMP, PNC (2019)
The recent passing of His Royal Highness Sultan Haji Ahmad Shah Al-Musta’in Billah Ibni Al-Marhum Sultan Abu Bakar Ri’ayatuddin Al-Mu’adzam Shah on May 22, 2019, was overwhelmingly felt by all across the State of Pahang Darul Makmur, especially by those at Universiti Malaysia Pahang (UMP).